REPRESENTASI DISABILITAS DALAM FILM ANIME “JOSEE, THE TIGER, AND THE FISH” MENGGUNAKAN ANALISIS SEMIOTIKA ROLAND BARTHES - Nur Windha Garnita; Suryanto Suryanto (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to analyze the representation of people with disabilities in the anime film Josee, the Tiger, and the Fish using Roland Barthes' semiotic approach. The study is motivated by the social perception that often simplifies people with disabilities into figures worthy of pity or mere inspiration, necessitating a critical examination of symbolic and narrative constructions in popular media. The research method applied is qualitative descriptive with a semiotic analysis strategy, where data were collected through in-depth observation of the film and literature review from various scientific references on disability representation and semiotics. The results indicate that the character Josee is represented multidimensionally, including emotional, social, and aspirational aspects, alongside visual and verbal symbols that convey an inclusive and humane understanding of people with disabilities. These findings emphasize the importance of sensitive and complex narratives in popular media to influence audience perception and provide a realistic understanding of the experiences of people with disabilities. In conclusion, the film not only entertains but also contributes to social and cultural learning about inclusivity, while encouraging media producers to create fairer characters and storylines.